2006
DOI: 10.1143/jjap.45.1219
|View full text |Cite
|
Sign up to set email alerts
|

High-Speed 7× CuSi-Based Write-Once Blu-ray Disc

Abstract: A Cu/Si bilayer can be applied as the recording medium in a write-once Blu-ray Disc (BD-R). Recording experiments performed on BD-R stacks showed that a 1/1 ratio of Cu/Si layers prove to have the best recording results. Auger analysis points to a diffusion-driven process, primarily that of Si into Cu. By optimization of the stack, we have been able to record 1–7× BD-R 25 GB discs with bottom jitters below 6.5% using a castle-type write strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 7 publications
0
13
1
Order By: Relevance
“…Typically, the wide power margin in the dynamic result shows that the optical disc can ensure superior optical drive compatibility. Compared to the previous study, 13 it can be found that the Si/CuSi blu-ray disc in our work has the wider recording power margin than that in Cu/Si blu-ray disc. This is attributed to the formation of c-Si crystallization at lower (270 C) and higher (500 C) annealed temperatures, and it results in the obvious changes in reflectivity and better dynamic behaviors at the relatively low and high writing powers.…”
contrasting
confidence: 66%
“…Typically, the wide power margin in the dynamic result shows that the optical disc can ensure superior optical drive compatibility. Compared to the previous study, 13 it can be found that the Si/CuSi blu-ray disc in our work has the wider recording power margin than that in Cu/Si blu-ray disc. This is attributed to the formation of c-Si crystallization at lower (270 C) and higher (500 C) annealed temperatures, and it results in the obvious changes in reflectivity and better dynamic behaviors at the relatively low and high writing powers.…”
contrasting
confidence: 66%
“…It is conjectured that if an NA value of 0.85 instead of 0.65 is used, as indicated in the 'blue-ray disk', the sizes in the direction along the on-land of dots written with peak powers of 3.5-5.5 mW will become less than 0.18 μm, corresponding to a storage capacity of 23GB/in. 2 [6,7]. Furthermore, it was observed that the embryo of a hole was faintly obtained in the dot at a peak power of 10.5 mW, and the holes then were clearly formed at the peak power of 11.5 mW, corresponding to a drastic drop of CNR at the peak power between 11.0 and 11.5 mW in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The energy gaps of recording films employed in WODs have become wider as the wavelength of the semiconductor laser to read and write information has become shorter from red (λ = 780-830 nm) to blue (λ~400 nm). A new area of interest is now rapidly developing as Cu-Si bilayers [1][2][3] and Bi-Ge-N alloy layers [4] are replacing dye layers as recording media in writeonce blue-ray disks. Oxide films, however, seem to be one of the most anticipated media [5] because of the following reasons: (1) superior duration under ambient temperatures and humidity conditions, (2) small transition time between different states caused by laser pulse irradiation, (3) a clear-cut edge around the dot formed in the films and (4) no-toxic to the surroundings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the formation and detection of appropriate record- ing marks, it is necessary to have materials, which can transform either from amorphous to crystalline phase or vice-versa with sufficient difference in reflectivity between these two states when exposed to laser pulses of suitable power. Materials that have been developed over the years for BDR applications are Cu/Si [5,7], SbSnIn, InSb and BiFeO [6]. We have established that inorganic Sb 100−x−y Sn x In y material when doped with certain percentage of ceramics ZnS-SiO 2 , could be used as the suitable material as phase change layer for the development of BDR L2H media.…”
Section: Introductionmentioning
confidence: 99%